Pertanggungjawaban Hukum Informed Consent dalam Perspektif Hukum Perdata Kesehatan - Nirmalasari, Lucia; Husain, Bahtiar; Sutrisno, Sutrisno (Dinasti Research, 2025)
This paper examines the legal liability aspects of the implementation of informed consent in medical practice in Indonesia from the perspective of civil health law. Informed consent is a form of approval for medical procedures given consciously and voluntarily by the patient after receiving sufficient information from medical personnel. The study focuses on the development of legal norms in Law Number 17 of 2023 on Health, which replaces Law Number 36 of 2009, and how the new regulation governs the rights and obligations within the informed consent process, particularly in situations where the patient is unable to provide consent directly. The paper also explores the role and legal status of guardians in providing informed consent, based on both general civil law and health law. This study is expected to contribute to the understanding of legal and medical practitioners in handling liability cases arising from failures in obtaining valid informed consent